Analisa Konsep Produktivitas Kerja Konvensional Dalam Pandangan Islam - Muhammad Ghozali; Khoirul Fathoni (Al Tijarah, 2017)
Productivity implies a comparison between the results achieved (outputs) with the overall resources used (input). In other words, productivity has two dimensions. The first dimension is the effectiveness that leads to achieving maximum performance is the achievement of targets relating to the quality, quantity, and time. The second is the efficiency related to attempt to compare the input actually used or how the work is performed. In Islam, a Muslim is encouraged to do something with the best performance, not only for himself but also for others. Because it is a measure of private productive. Islam encourages his people to produce and play a role in various forms of economic activity. Islam bless the work of this world and make it part of worship and jihad. By working, people can meet their needs, provide for his family and doing good to their neighbors. In other words that the work should bring goodness in the context of worship and hope keridloan of Allah SWT.